Analisis Kebijakan Dividen dan Corporate Governance terhadap Nilai Perusahaan Studi Kasus Perusahaan Bumn yang terdaftar di Bei - Dwi Iroah; Siti Muntahanah; Isnaeni Rokhayati (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
The main objective of the company is to maximise the value of the company. But a company can fail to increase company value, if it is not careful in applying the factors that affect company value. The purpose of this study was to determine the effect of dividend policy, institutional ownership, managerial ownership and audit committee on firm value proxied by TobinQ. The sample of this study is state-owned companies listed on the IDX for the period 2015-2021 with a total of 24 companies using purposive sampling method. Using the classic assumption test analysis method and hypothesis testing and multiple analysis, the analytical tool used is multiple linear regression panel data with the best model, namely the fixed effect model. The results showed that the t test for dividend policy was 2.375568 and the t table was 1.697 where t count> t table and a significant probability number of 0.025 <0.05 which means that dividend policy has a positive and significant effect on firm value. While institutional ownership, managerial ownership and audit committee have no significant effect on firm value. The F test results explain that the selected model is suitable for use in research. Then the results of the regression coefficient test (R²) indicate that the predictive ability of the 4 independent variables is 82.98%, while the remaining 17.02% is influenced by other factors outside the model which is not significant.